Self-healing agent for well cementation cement slurry and preparation method of self-healing agent

By using cementing cementing slurry self-healing agents with modified polyethylene terephthalate-based polymers and other components, the problems of low self-healing efficiency and short-term repair in the prior art are solved, and efficient self-healing and long-term stability under extreme conditions are achieved.

CN119898990AActive Publication Date: 2025-04-29SICHUAN ANNUS OIL & GAS ENERGY TECH CO LTD

Patent Information

Application Number
CN202510377249.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2025-04-29
Estimated Expiration
2045-03-28

AI Technical Summary

Technical Problem

The existing cementing cement slurry self-healing agent has low self-healing efficiency under extreme conditions such as high temperature, high pressure, high salt, etc., and the repair products may be damaged or dissolved under long-term formation stress and fluid erosion, resulting in the reappearance of cracks and inability to achieve long-term effective repair.

Method used

Modified polyethylene terephthalate-based polymer, metal oxide, lithium silicate, persulfate, Bacillus subtilis and calcium lactate are used as components to form materials with high reactive activity and strong self-healing ability through alcoholylation and hydrolysis polycondensation reaction.

Benefits of technology

The self-healing efficiency is significantly improved under extreme conditions, and the repair products formed have higher stability and impact resistance, which can effectively repair cracks in the long term and improve the long-term stability and sealing performance of the cementing structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of self-healing agents, in particular to a well cementation cement slurry self-healing agent and a preparation method thereof. The modified polyethylene glycol terephthalate polymer comprises the following components in parts by weight: 30-50 parts of modified polyethylene glycol terephthalate polymer, 2-10 parts of metal oxide, 5-15 parts of lithium silicate, 0.5-2 parts of persulfate, 0.1-1 part of bacillus subtilis and 1-5 parts of calcium lactate. The isosorbide can react with ester bonds in polyethylene glycol terephthalate, so that more hydroxyl groups are introduced, and the hydroxyl groups can interact with cement hydration products or metal oxides and lithium silicate to promote formation of new mineral phases at cracks. The generation of the new mineral phase is beneficial to filling and repairing cracks, and the self-healing of the cement paste is realized, so that the long-term stability of a well cementation structure is improved. Tetraethyl orthosilicate can cooperate with other components such as the modified polyethylene glycol terephthalate polymer to jointly promote the self-healing process of set cement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of self-healing agents, in particular to a self-healing agent for cementing slurry and a preparation method thereof. Background Art

[0002] In the field of oil and gas extraction, cementing operations are the key link to ensure the long-term stability of the wellbore, prevent the crossflow of formation fluids, and protect the casing. As the core material for forming the cement sheath, the performance of cementing slurry directly affects the production life and safety of the entire oil and gas well. However, with the drastic changes in temperature and pressure during the production of oil and gas wells, as well as the long-term erosion of formation fluids, the cement sheath is very prone to cracks. These cracks will not only cause the leakage of formation fluids and reduce the production efficiency of oil and gas wells, but may also cause serious safety hazards, such as wellhead loss of control and environmental pollution. Traditional cementing slurry cannot be effectively repaired by itself after cracks occur, and a lot of manpower, material resources and time are required for remedial measures such as secondary cementing, which greatly increases the cost of extraction. Self-healing technology, as an emerging solution, aims to give materials the ability to self-repair, automatically close tiny cracks through internal mechanisms, and restore the integrity and functionality of the structure.

[0003] Although some existing cementing cement slurry self-healing agents can improve the crack repair ability of cement slurry to a certain extent, they still have many shortcomings; the repair effect of some self-healing agents is greatly affected by downhole environmental factors. Under extreme conditions such as high temperature, high pressure, and high salt, the self-healing efficiency is greatly reduced; the repair products formed by some self-healing agents may gradually be destroyed or dissolved under long-term formation stress and fluid scouring, causing cracks to reappear, and long-term effective repair cannot be achieved. In view of this, we propose a cementing cement slurry self-healing agent and a preparation method thereof. Summary of the invention

[0004] The purpose of the present invention is to provide a self-healing agent for cementing slurry and a preparation method thereof, so as to solve the problem proposed in the above background technology that the repair effect of some self-healing agents is greatly affected by downhole environmental factors, and the self-healing efficiency is greatly reduced under extreme conditions such as high temperature, high pressure, and high salt; the repair products formed by some self-healing agents may gradually be destroyed or dissolved under long-term formation stress and fluid scouring, causing the cracks to reappear, and long-term effective repair cannot be achieved.

[0005] To achieve the above object, the present invention provides a cementing slurry self-healing agent, comprising the following components: 30-50 parts by weight of a modified polyethylene terephthalate-based polymer, 2-10 parts by weight of a metal oxide, 5-15 parts by weight of a lithium silicate, 0.5-2 parts by weight of a persulfate, 0.1-1 parts by weight of Bacillus subtilis and 1-5 parts by weight of calcium lactate; The modified polyethylene terephthalate-based polymer is prepared by alcoholysis reaction of isosorbide and polyethylene terephthalate, and then mixing with tetraethyl orthosilicate and titanate.

[0006] Preferably, the preparation method of the modified polyethylene terephthalate-based polymer is as follows: S1.1, respectively weigh the following components in parts by weight: 50-80 parts by weight of polyethylene terephthalate, 10-30 parts by weight of isosorbide, 1-3 parts by weight of sodium hydroxide, 10-20 parts by weight of tetraethyl orthosilicate, 20-40 parts by weight of toluene, 5-15 parts by weight of titanate, and 0.1-0.5 parts by weight of acetic acid; S1.2, under nitrogen protection, polyethylene terephthalate and isosorbide are mixed, sodium hydroxide with a concentration of 1-3% is added, the temperature is slowly raised to 180-250°C, and agitated at a speed of 300-600 r / min for 3-8 hours to obtain modified polyethylene terephthalate; During the alcoholysis reaction, the ester bonds of polyethylene terephthalate (PET) are broken and combined with isosorbide to form new ester bonds. This process introduces a large number of hydroxyl groups (-OH) into the product, significantly improving the hydrophilicity of the material and making it more absorbing. This means that the modified PET can better absorb and store water, thus providing advantages in various complex environments. In addition, these hydroxyl groups give the material a higher chemical reactivity, creating favorable conditions for subsequent reactions with other functional components (such as siloxanes, titanates, etc.). Through these subsequent reactions, a more complex network structure with multiple functions can be constructed, thereby enhancing the comprehensive performance of the material.

[0007] In cementing operations, modified polyethylene terephthalate can serve as an important source of moisture, continuously providing the required moisture for the secondary hydration reaction of cement. This continuous moisture supply can prolong the duration of the self-healing effect of cement stone and provide more lasting protection for the cementing structure. The longer flexible chain segments of isosorbide are introduced into the modified polyethylene terephthalate after the alcoholysis reaction. These segments bring higher flexibility and stronger impact resistance to the material, greatly reducing the possibility of material fracture due to brittleness and improving the overall reliability of the material.

[0008] S1.3, dissolving tetraethyl orthosilicate in toluene to obtain a tetraethyl orthosilicate solution; adding modified polyethylene terephthalate to the tetraethyl orthosilicate solution, lowering the temperature to 80-120° C., and stirring at a speed of 400-800 r / min for 30-60 min to obtain a mixture; Under specific conditions, tetraethyl orthosilicate is hydrolyzed and polycondensed to form a siloxane network structure. After mixing with modified polyethylene terephthalate, the formed siloxane network can interact with the functional groups (such as hydroxyl groups) in the modified PET. This interaction constructs an organic-inorganic hybrid network structure at the molecular level, giving the material both the flexibility of organic materials and the rigidity and stability of inorganic materials. In addition, the silica products generated by the hydrolysis of tetraethyl orthosilicate can fill the gaps between the modified PET molecular chains, making the material denser, reducing the porosity, and significantly improving the mechanical properties of the material, such as compressive strength and flexural strength. At the same time, this filling effect can also effectively prevent the penetration and diffusion of small molecules (such as gases or liquids) and enhance the barrier properties of the material. For cementing cement slurry self-healing agents, this property helps to reduce the cross-flow of fluids such as oil and gas in the cement ring.

[0009] When cracks appear in the material, the silica products generated by the hydrolysis of ethyl orthosilicate can react with the active groups in the modified PET and the moisture in the environment to form new chemical bonds or physical bonds, thereby filling the cracks and realizing self-healing function, ensuring the integrity and functionality of the material.

[0010] S1.4, add titanate to the mixture, add 98% acetic acid after the addition, and continue stirring at 400-800r / min for 10-15min; after mixing evenly, raise the temperature to 120-150℃ and react for 1-3h; Titanates may react with active groups (such as hydroxyl groups, silanol groups, etc.) in modified polyethylene terephthalate or ethyl orthosilicate hydrolyzates to generate chemical bonds with higher bond energy and stronger interaction force, thereby improving the strength and hardness of the material, which is crucial for cementing cement slurry self-healing agents, because higher strength and hardness can enable cement stone to better withstand formation pressure and resist rock extrusion on the cement ring, preventing deformation and damage to the cement ring; titanates may react with acids to generate stable compounds and form a stable passivation film on the surface of the material to prevent acidic substances from further corroding the interior of the material, ensuring the structural integrity and performance stability of the material; titanates can participate in the self-healing process of the material. When cracks appear in the material, the titanium element in the titanate can react with substances in the environment to form new repair substances, fill the cracks, and improve the self-healing ability and effect of the material.

[0011] S1.5. After the reaction is completed, the reaction system is subjected to rotary evaporation at 50-80°C and a vacuum degree of 0.08-0.1 MPa to obtain a modified polyethylene terephthalate-based polymer.

[0012] Preferably, in S1.2, the relative molecular mass of polyethylene terephthalate is between 15000 and 30000.

[0013] Preferably, in S1.2, the rate of slowly increasing the temperature is 20-30°C / h.

[0014] Preferably, in S1.3, the concentration of the ethyl orthosilicate solution is 30-70%.

[0015] Preferably, in S1.4, the titanate is any one of tetrabutoxy titanate or tetraisopropoxy titanate.

[0016] Preferably, in S1.4, the time for adding titanate dropwise is 20-40 min.

[0017] On the other hand, the present invention provides a method for preparing a cementing slurry self-healing agent, which is used to prepare the cementing slurry self-healing agent, comprising the following steps: S2.1. Weigh the following components in parts by weight respectively: 30-50 parts by weight of modified polyethylene terephthalate-based polymer, 2-10 parts by weight of metal oxide, 5-15 parts by weight of lithium silicate, 0.5-2 parts by weight of persulfate, 0.1-1 parts by weight of Bacillus subtilis and 1-5 parts by weight of calcium lactate; S2.2, uniformly mixing the modified polyethylene terephthalate-based polymer, the metal oxide, the lithium silicate and the persulfate, stirring with a stirrer at a speed of 100-200 rpm for 20-30 min to obtain a dry blend; S2.3, slowly drop the activated Bacillus subtilis suspension into the dry mix, and stir at a speed of 200-300 rpm for 5-10 min; add calcium lactate, and continue stirring at a speed of 200-300 rpm for 10-20 min to obtain a mixture; Bacillus subtilis is resistant to highly alkaline environments, and the pH value of cement slurry is usually between 11-12 at the beginning, which is a strong alkaline environment. Bacillus subtilis can survive in this environment. During the metabolism process, Bacillus subtilis produces urease to decompose urea into ammonia and carbonate ions, which combine with Ca²⁺ in the environment to accelerate the precipitation process of calcium carbonate; calcium carbonate is a common filling material that can fill cracks and pores in cement slurry and realize self-healing function, thereby improving the sealing and strength of cement slurry; in addition, calcium lactate can adjust the pH value of the mixture to a certain extent, creating a suitable living environment for microorganisms such as Bacillus subtilis, ensuring their normal metabolic activities, and facilitating the self-healing agent to achieve the best effect.

[0018] S2.4. Place the mixture in an oven and dry it at 40-60°C for 1-2 days to obtain a cementing slurry self-healing agent.

[0019] Preferably, in S2.2, the metal oxide is zinc oxide or magnesium oxide.

[0020] Preferably, in S2.3, the activated Bacillus subtilis suspension is slowly added to the dry mix at a rate of 1-5 mL / min.

[0021] Compared with the prior art, the present invention has the following beneficial effects: 1. In the cementing cement slurry self-healing agent and its preparation method, the addition of isosorbide can react with the ester bonds in polyethylene terephthalate, thereby introducing more hydroxyl groups. These hydroxyl groups can interact with cement hydration products or other additives (such as metal oxides, lithium silicates, etc.) to promote the formation of new mineral phases at the cracks. The generation of this new mineral phase helps to fill and repair cracks, achieve self-healing of cement slurry, and thus improve the long-term stability of the cementing structure.

[0022] 2. In the cementing cement slurry self-healing agent and its preparation method, after adding tetraethyl orthosilicate, the silica gel produced by its hydrolysis and condensation can form colloidal particles in the cracks; as time goes by, these colloidal particles will gradually aggregate and solidify, thereby filling the cracks and realizing the self-healing of the cement stone; tetraethyl orthosilicate can synergistically act with other components such as modified polyethylene terephthalate-based polymers and metal oxides to jointly promote the self-healing process of the cement stone.

[0023] 3. In the cementing cement slurry self-healing agent and its preparation method, after adding titanate, it can react with the components in cement to generate substances with gelling properties, such as calcium titanate, etc. These substances can fill the pores and microcracks inside the cement stone, making the structure of the cement stone denser, thereby improving the compressive strength and flexural strength of the cement stone. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] The present invention provides a cementing slurry self-healing agent, comprising the following components: 30-50 parts by weight of a modified polyethylene terephthalate-based polymer, 2-10 parts by weight of a metal oxide, 5-15 parts by weight of a lithium silicate, 0.5-2 parts by weight of a persulfate, 0.1-1 parts by weight of Bacillus subtilis, and 1-5 parts by weight of calcium lactate; The modified polyethylene terephthalate-based polymer is prepared by alcoholysis reaction of isosorbide and polyethylene terephthalate, and then mixing with tetraethyl orthosilicate and titanate.

[0026] The titanate is any one of tetrabutoxy titanate or tetraisopropoxy titanate, preferably tetrabutoxy titanate.

[0027] The metal oxide is zinc oxide or magnesium oxide, preferably zinc oxide.

[0028] Activated Bacillus subtilis suspension: Use LB medium and shake culture at 150 rpm at 37°C for 24 hours to grow Bacillus subtilis to the logarithmic phase; after the culture is completed, centrifuge the cultured bacterial solution at 4000 rpm for 10 minutes to separate the bacterial precipitate; resuspend the bacterial precipitate with sterile saline to make a concentration of 10 7 CFU / mL of Bacillus subtilis suspension is ready for use.

[0029] Embodiment 1: A method for preparing a cement slurry self-healing agent, comprising the following steps: S2.1. Weigh the following components in parts by weight respectively: 40 parts by weight of modified polyethylene terephthalate-based polymer, 6 parts by weight of zinc oxide, 10 parts by weight of lithium silicate, 1.2 parts by weight of persulfate, 0.5 parts by weight of Bacillus subtilis and 3 parts by weight of calcium lactate; S2.2, uniformly mixing the modified polyethylene terephthalate-based polymer, zinc oxide, lithium silicate and persulfate, and stirring with a stirrer at a speed of 200 rpm for 30 min to obtain a dry blend; S2.3, add the activated Bacillus subtilis suspension to the dry mix at a rate of 3 mL / min, and stir at a rate of 300 rpm for 10 min; add calcium lactate, and continue stirring at a rate of 300 rpm for 20 min to obtain a mixture; S2.4. Place the mixture in an oven and dry it at 60°C for 2 days to obtain a cementing slurry self-healing agent.

[0030] The preparation method of the modified polyethylene terephthalate-based polymer is as follows: S1.1. Weigh the following components in parts by weight respectively: 65 parts by weight of polyethylene terephthalate, 13 parts by weight of isosorbide, 2 parts by weight of sodium hydroxide, 15 parts by weight of tetraethyl orthosilicate, 30 parts by weight of toluene, 10 parts by weight of tetrabutoxy titanate and 0.3 parts by weight of acetic acid; S1.2, under nitrogen protection, polyethylene terephthalate with a relative molecular mass of 20,000 was mixed with isosorbide, sodium hydroxide with a concentration of 2% was added, the temperature was raised to 220°C at a rate of 25°C / h, and the mixture was stirred at a speed of 500 r / min for 6 hours to obtain modified polyethylene terephthalate; S1.3, dissolving tetraethyl orthosilicate in toluene to obtain a 50% tetraethyl orthosilicate solution; adding modified polyethylene terephthalate to the tetraethyl orthosilicate solution, lowering the temperature to 120°C, and stirring at a speed of 600 r / min for 60 min to obtain a mixture; S1.4, add tetrabutoxy titanate to the mixture dropwise for 40 minutes; after the addition is completed, add acetic acid with a concentration of 98%, and continue to stir at a speed of 800r / min for 15 minutes; after mixing evenly, raise the temperature to 150℃ and react for 3 hours; S1.5. After the reaction is completed, the reaction system is subjected to rotary evaporation at 60° C. and a vacuum degree of 0.1 MPa to obtain a modified polyethylene terephthalate-based polymer.

[0031] Embodiment 2: A method for preparing a cementing slurry self-healing agent, comprising the following steps: S2.1. Weigh the following components in parts by weight respectively: 40 parts by weight of modified polyethylene terephthalate-based polymer, 6 parts by weight of zinc oxide, 10 parts by weight of lithium silicate, 1.2 parts by weight of persulfate, 0.5 parts by weight of Bacillus subtilis and 3 parts by weight of calcium lactate; S2.2, uniformly mixing the modified polyethylene terephthalate-based polymer, zinc oxide, lithium silicate and persulfate, and stirring with a stirrer at a speed of 200 rpm for 30 min to obtain a dry blend; S2.3, add the activated Bacillus subtilis suspension to the dry mix at a rate of 3 mL / min, and stir at a rate of 300 rpm for 10 min; add calcium lactate, and continue stirring at a rate of 300 rpm for 20 min to obtain a mixture; S2.4. Place the mixture in an oven and dry it at 60°C for 2 days to obtain a cementing slurry self-healing agent.

[0032] The preparation method of the modified polyethylene terephthalate-based polymer is as follows: S1.1. Weigh the following components in parts by weight respectively: 65 parts by weight of polyethylene terephthalate, 20 parts by weight of isosorbide, 2 parts by weight of sodium hydroxide, 15 parts by weight of tetraethyl orthosilicate, 30 parts by weight of toluene, 10 parts by weight of tetrabutoxy titanate and 0.3 parts by weight of acetic acid; S1.2, under nitrogen protection, polyethylene terephthalate with a relative molecular mass of 20,000 was mixed with isosorbide, sodium hydroxide with a concentration of 2% was added, the temperature was raised to 220°C at a rate of 25°C / h, and the mixture was stirred at a speed of 500 r / min for 6 hours to obtain modified polyethylene terephthalate; S1.3, dissolving tetraethyl orthosilicate in toluene to obtain a 50% tetraethyl orthosilicate solution; adding modified polyethylene terephthalate to the tetraethyl orthosilicate solution, lowering the temperature to 120°C, and stirring at a speed of 600 r / min for 60 min to obtain a mixture; S1.4, add tetrabutoxy titanate to the mixture dropwise for 40 minutes; after the addition is completed, add acetic acid with a concentration of 98%, and continue to stir at a speed of 800r / min for 15 minutes; after mixing evenly, raise the temperature to 150℃ and react for 3 hours; S1.5. After the reaction is completed, the reaction system is subjected to rotary evaporation at 60° C. and a vacuum degree of 0.1 MPa to obtain a modified polyethylene terephthalate-based polymer.

[0033] Embodiment 3: A method for preparing a cementing slurry self-healing agent, comprising the following steps: S2.1. Weigh the following components in parts by weight respectively: 40 parts by weight of modified polyethylene terephthalate-based polymer, 6 parts by weight of zinc oxide, 10 parts by weight of lithium silicate, 1.2 parts by weight of persulfate, 0.5 parts by weight of Bacillus subtilis and 3 parts by weight of calcium lactate; S2.2, uniformly mixing the modified polyethylene terephthalate-based polymer, zinc oxide, lithium silicate and persulfate, and stirring with a stirrer at a speed of 200 rpm for 30 min to obtain a dry blend; S2.3, add the activated Bacillus subtilis suspension to the dry mix at a rate of 3 mL / min, and stir at a rate of 300 rpm for 10 min; add calcium lactate, and continue stirring at a rate of 300 rpm for 20 min to obtain a mixture; S2.4. Place the mixture in an oven and dry it at 60°C for 2 days to obtain a cementing slurry self-healing agent.

[0034] The preparation method of the modified polyethylene terephthalate-based polymer is as follows: S1.1. Weigh the following components in parts by weight respectively: 65 parts by weight of polyethylene terephthalate, 26 parts by weight of isosorbide, 2 parts by weight of sodium hydroxide, 15 parts by weight of tetraethyl orthosilicate, 30 parts by weight of toluene, 10 parts by weight of tetrabutoxy titanate and 0.3 parts by weight of acetic acid; S1.2, under nitrogen protection, polyethylene terephthalate with a relative molecular mass of 20,000 was mixed with isosorbide, sodium hydroxide with a concentration of 2% was added, the temperature was raised to 220°C at a rate of 25°C / h, and the mixture was stirred at a speed of 500 r / min for 6 hours to obtain modified polyethylene terephthalate; S1.3, dissolving tetraethyl orthosilicate in toluene to obtain a 50% tetraethyl orthosilicate solution; adding modified polyethylene terephthalate to the tetraethyl orthosilicate solution, lowering the temperature to 120°C, and stirring at a speed of 600 r / min for 60 min to obtain a mixture; S1.4, add tetrabutoxy titanate to the mixture dropwise for 40 minutes; after the addition is completed, add acetic acid with a concentration of 98%, and continue to stir at a speed of 800r / min for 15 minutes; after mixing evenly, raise the temperature to 150℃ and react for 3 hours; S1.5. After the reaction is completed, the reaction system is subjected to rotary evaporation at 60° C. and a vacuum degree of 0.1 MPa to obtain a modified polyethylene terephthalate-based polymer.

[0035] Embodiment 4: A method for preparing a cementing slurry self-healing agent, comprising the following steps: S2.1. Weigh the following components in parts by weight respectively: 40 parts by weight of modified polyethylene terephthalate-based polymer, 6 parts by weight of zinc oxide, 10 parts by weight of lithium silicate, 1.2 parts by weight of persulfate, 0.5 parts by weight of Bacillus subtilis and 3 parts by weight of calcium lactate; S2.2, uniformly mixing the modified polyethylene terephthalate-based polymer, zinc oxide, lithium silicate and persulfate, and stirring with a stirrer at a speed of 200 rpm for 30 min to obtain a dry blend; S2.3, add the activated Bacillus subtilis suspension to the dry mix at a rate of 3 mL / min, and stir at a rate of 300 rpm for 10 min; add calcium lactate, and continue stirring at a rate of 300 rpm for 20 min to obtain a mixture; S2.4. Place the mixture in an oven and dry it at 60°C for 2 days to obtain a cementing slurry self-healing agent.

[0036] The preparation method of the modified polyethylene terephthalate-based polymer is as follows: S1.1. Weigh the following components in parts by weight respectively: 65 parts by weight of polyethylene terephthalate, 30 parts by weight of isosorbide, 2 parts by weight of sodium hydroxide, 15 parts by weight of tetraethyl orthosilicate, 30 parts by weight of toluene, 10 parts by weight of tetrabutoxy titanate and 0.3 parts by weight of acetic acid; 13 19.5 26 30 S1.2, under nitrogen protection, polyethylene terephthalate with a relative molecular mass of 20,000 was mixed with isosorbide, sodium hydroxide with a concentration of 2% was added, the temperature was raised to 220°C at a rate of 25°C / h, and the mixture was stirred at a speed of 500 r / min for 6 hours to obtain modified polyethylene terephthalate; S1.3, dissolving tetraethyl orthosilicate in toluene to obtain a 50% tetraethyl orthosilicate solution; adding modified polyethylene terephthalate to the tetraethyl orthosilicate solution, lowering the temperature to 120°C, and stirring at a speed of 600 r / min for 60 min to obtain a mixture; S1.4, add tetrabutoxy titanate to the mixture dropwise for 40 minutes; after the addition is completed, add acetic acid with a concentration of 98%, and continue to stir at a speed of 800r / min for 15 minutes; after mixing evenly, raise the temperature to 150℃ and react for 3 hours; S1.5. After the reaction is completed, the reaction system is subjected to rotary evaporation at 60° C. and a vacuum degree of 0.1 MPa to obtain a modified polyethylene terephthalate-based polymer.

[0037] Embodiment 5: A method for preparing a cementing slurry self-healing agent, comprising the following steps: S2.1. Weigh the following components in parts by weight respectively: 30 parts by weight of modified polyethylene terephthalate-based polymer, 2 parts by weight of zinc oxide, 5 parts by weight of lithium silicate, 0.5 parts by weight of persulfate, 0.1 parts by weight of Bacillus subtilis and 1 part by weight of calcium lactate; S2.2, uniformly mixing the modified polyethylene terephthalate-based polymer, zinc oxide, lithium silicate and persulfate, and stirring with a stirrer at a speed of 200 rpm for 30 min to obtain a dry blend; S2.3, add the activated Bacillus subtilis suspension to the dry mix at a rate of 3 mL / min, and stir at a rate of 300 rpm for 10 min; add calcium lactate, and continue stirring at a rate of 300 rpm for 20 min to obtain a mixture; S2.4. Place the mixture in an oven and dry it at 60°C for 2 days to obtain a cementing slurry self-healing agent.

[0038] The preparation method of the modified polyethylene terephthalate-based polymer is as follows: S1.1. Weigh the following components in parts by weight respectively: 65 parts by weight of polyethylene terephthalate, 26 parts by weight of isosorbide, 1 part by weight of sodium hydroxide, 10 parts by weight of tetraethyl orthosilicate, 20 parts by weight of toluene, 5 parts by weight of tetrabutoxy titanate and 0.1 parts by weight of acetic acid; S1.2, under nitrogen protection, polyethylene terephthalate with a relative molecular mass of 20,000 was mixed with isosorbide, sodium hydroxide with a concentration of 1% was added, the temperature was raised to 220°C at a rate of 25°C / h, and the mixture was stirred at a speed of 500 r / min for 6 hours to obtain modified polyethylene terephthalate; S1.3, dissolving tetraethyl orthosilicate in toluene to obtain a 30% tetraethyl orthosilicate solution; adding modified polyethylene terephthalate to the tetraethyl orthosilicate solution, lowering the temperature to 120°C, and stirring at a speed of 600 r / min for 60 min to obtain a mixture; S1.4, add tetrabutoxy titanate to the mixture dropwise for 40 minutes; after the addition is completed, add acetic acid with a concentration of 98%, and continue to stir at a speed of 800r / min for 15 minutes; after mixing evenly, raise the temperature to 150℃ and react for 3 hours; S1.5. After the reaction is completed, the reaction system is subjected to rotary evaporation at 60° C. and a vacuum degree of 0.1 MPa to obtain a modified polyethylene terephthalate-based polymer.

[0039] Embodiment 6: A method for preparing a cementing slurry self-healing agent, comprising the following steps: S2.1. Weigh the following components in parts by weight respectively: 40 parts by weight of modified polyethylene terephthalate-based polymer, 2 parts by weight of zinc oxide, 5 parts by weight of lithium silicate, 0.5 parts by weight of persulfate, 0.1 parts by weight of Bacillus subtilis and 1 part by weight of calcium lactate; S2.2, uniformly mixing the modified polyethylene terephthalate-based polymer, zinc oxide, lithium silicate and persulfate, and stirring with a stirrer at a speed of 200 rpm for 30 min to obtain a dry blend; S2.3, add the activated Bacillus subtilis suspension to the dry mix at a rate of 3 mL / min, and stir at a rate of 300 rpm for 10 min; add calcium lactate, and continue stirring at a rate of 300 rpm for 20 min to obtain a mixture; S2.4. Place the mixture in an oven and dry it at 60°C for 2 days to obtain a cementing slurry self-healing agent.

[0040] The preparation method of the modified polyethylene terephthalate-based polymer is as follows: S1.1. Weigh the following components in parts by weight respectively: 65 parts by weight of polyethylene terephthalate, 26 parts by weight of isosorbide, 1 part by weight of sodium hydroxide, 10 parts by weight of tetraethyl orthosilicate, 20 parts by weight of toluene, 5 parts by weight of tetrabutoxy titanate and 0.1 parts by weight of acetic acid; S1.2, under nitrogen protection, polyethylene terephthalate with a relative molecular mass of 20,000 was mixed with isosorbide, sodium hydroxide with a concentration of 1% was added, the temperature was raised to 220°C at a rate of 25°C / h, and the mixture was stirred at a speed of 500 r / min for 6 hours to obtain modified polyethylene terephthalate; S1.3, dissolving tetraethyl orthosilicate in toluene to obtain a 30% tetraethyl orthosilicate solution; adding modified polyethylene terephthalate to the tetraethyl orthosilicate solution, lowering the temperature to 120°C, and stirring at a speed of 600 r / min for 60 min to obtain a mixture; S1.4, add tetrabutoxy titanate to the mixture dropwise for 40 minutes; after the addition is completed, add acetic acid with a concentration of 98%, and continue to stir at a speed of 800r / min for 15 minutes; after mixing evenly, raise the temperature to 150℃ and react for 3 hours; S1.5. After the reaction is completed, the reaction system is subjected to rotary evaporation at 60° C. and a vacuum degree of 0.1 MPa to obtain a modified polyethylene terephthalate-based polymer.

[0041] Embodiment 7: A method for preparing a cementing slurry self-healing agent, comprising the following steps: S2.1. Weigh the following components in parts by weight respectively: 50 parts by weight of modified polyethylene terephthalate-based polymer, 2 parts by weight of zinc oxide, 5 parts by weight of lithium silicate, 0.5 parts by weight of persulfate, 0.1 parts by weight of Bacillus subtilis and 1 part by weight of calcium lactate; S2.2, uniformly mixing the modified polyethylene terephthalate-based polymer, zinc oxide, lithium silicate and persulfate, and stirring with a stirrer at a speed of 200 rpm for 30 min to obtain a dry blend; S2.3, add the activated Bacillus subtilis suspension to the dry mix at a rate of 3 mL / min, and stir at a rate of 300 rpm for 10 min; add calcium lactate, and continue stirring at a rate of 300 rpm for 20 min to obtain a mixture; S2.4. Place the mixture in an oven and dry it at 60°C for 2 days to obtain a cementing slurry self-healing agent.

[0042] The preparation method of the modified polyethylene terephthalate-based polymer is as follows: S1.1. Weigh the following components in parts by weight respectively: 65 parts by weight of polyethylene terephthalate, 26 parts by weight of isosorbide, 1 part by weight of sodium hydroxide, 10 parts by weight of tetraethyl orthosilicate, 20 parts by weight of toluene, 5 parts by weight of tetrabutoxy titanate and 0.1 parts by weight of acetic acid; S1.2, under nitrogen protection, polyethylene terephthalate with a relative molecular mass of 20,000 was mixed with isosorbide, sodium hydroxide with a concentration of 1% was added, the temperature was raised to 220°C at a rate of 25°C / h, and the mixture was stirred at a speed of 500 r / min for 6 hours to obtain modified polyethylene terephthalate; S1.3, dissolving tetraethyl orthosilicate in toluene to obtain a 30% tetraethyl orthosilicate solution; adding modified polyethylene terephthalate to the tetraethyl orthosilicate solution, lowering the temperature to 120°C, and stirring at a speed of 600 r / min for 60 min to obtain a mixture; S1.4, add tetrabutoxy titanate to the mixture dropwise for 40 minutes; after the addition is completed, add acetic acid with a concentration of 98%, and continue to stir at a speed of 800r / min for 15 minutes; after mixing evenly, raise the temperature to 150℃ and react for 3 hours; S1.5. After the reaction is completed, the reaction system is subjected to rotary evaporation at 60° C. and a vacuum degree of 0.1 MPa to obtain a modified polyethylene terephthalate-based polymer. Comparative Example 1

[0043] The method of Example 3 is adopted, but the modified polyethylene terephthalate-based polymer is not used, and polyethylene terephthalate is directly used to prepare polyethylene terephthalate. Comparative Example 2

[0044] The method of Example 3 is adopted to remove tetraethyl orthosilicate in the preparation method of the modified polyethylene terephthalate-based polymer. Comparative Example 3

[0045] The method of Example 3 is adopted to remove the titanate in the preparation method of the modified polyethylene terephthalate-based polymer.

[0046] The present invention discloses a cementing slurry self-healing agent prepared by modifying a polyethylene terephthalate-based polymer, wherein the performance index test items and test standards of the cementing slurry self-healing agent are as follows: According to GB / T 50082-2009 standard, cement stone specimens of standard size (100×100×400 mm) were prepared, and cracks with a width of 0.5 mm and a length of 100 mm were made on the specimens using a cutting tool. The cracked specimens were completely immersed in a self-healing agent, and the width was observed after 28 days. The crack healing rate was calculated using a formula. A high crack healing rate indicates that the self-healing agent can effectively seal the cracks and reduce the infiltration of moisture, gas and other harmful substances, thereby improving the integrity and durability of the structure.

[0047] According to GB / T 50082-2009 standard, cement stone specimens of standard size (100×100×400 mm) were prepared, and cracks with a width of 0.5 mm and a length of 100 mm were made on the specimens using cutting tools. Professional permeability testers (such as constant pressure head permeameter) were used for measurement, and the permeability recovery rate was calculated using a formula. A high permeability recovery rate means that the self-healed cement stone has regained good sealing properties, preventing fluid leakage and reducing the risk of environmental pollution.

[0048] According to the above standards, the cementing slurry self-healing agents prepared in the above Examples 1-7 and Comparative Examples 1-3 were tested, and the obtained data are shown in Table 1: Table 1 Performance data of cement slurry self-healing agent of Examples 1-7 and Comparative Examples 1-3;

[0049] It can be seen from Examples 1-4 that: when the mass ratio of isosorbide to polyethylene terephthalate in the modified polyethylene terephthalate-based polymer gradually increases, the crack healing rate and permeability recovery rate of the cementing cement slurry self-healing agent gradually increase, but when the mass ratio of isosorbide to polyethylene terephthalate reaches a certain value, the crack healing rate and permeability recovery rate of the cementing cement slurry self-healing agent gradually decrease. It can be seen that with the increase of the mass ratio of isosorbide, the crack healing rate and permeability recovery rate of the cementing cement slurry self-healing agent are improved, but excessive increase may reduce the crack healing rate and permeability recovery rate of the cementing cement slurry self-healing agent; Isosorbide contains multiple hydroxyl (-OH) functional groups and has high reactivity. When the mass ratio of isosorbide to polyethylene terephthalate increases, the hydroxyl content in the system increases relatively, and it can react with calcium ions in cement hydration products to generate more substances with gelling properties. These substances can fill cracks, thereby improving the crack healing rate and permeability recovery rate. In addition, the addition of isosorbide can improve the flexibility and adhesion of the polymer, and can better adapt to the deformation and expansion of cracks. At the same time, its bonding performance with cement stone is also enhanced, so that the self-healing agent can adhere more firmly to the crack surface, effectively preventing the penetration of fluids, thereby improving the permeability recovery rate. Moreover, the improvement in flexibility helps the self-healing agent to form a continuous healing layer in the crack, thereby improving the healing effect of the crack.

[0050] Furthermore, by comparing Examples 5-7, it can be seen that when other components remain unchanged, only when the proportion of modified polyethylene terephthalate-based polymer gradually increases, the crack healing rate and permeability recovery rate of the cementing cement slurry self-healing agent gradually increase. It can be seen that the modified polyethylene terephthalate-based polymer has significant flexibility and viscosity. When its proportion increases, it can flow better into the cracks of the cement stone to form effective filling. This filling not only directly reduces the width and length of the cracks, thereby improving the crack healing rate; as the proportion of modified polyethylene terephthalate-based polymer increases, after filling the cracks, the permeability of the cracks can be reduced, preventing the fluid from passing through. Penetrate through the cracks, thereby improving the permeability recovery rate; modified polyethylene terephthalate-based polymers can play a role similar to that of a toughening agent in cement slurry, which helps to improve the microstructure of cement stone and make it denser. This dense structure can not only improve the strength of cement stone, but also reduce the generation and expansion of cracks, thereby improving the crack healing rate and permeability recovery rate; in addition, modified polyethylene terephthalate-based polymers can also provide more material and energy support for the self-healing reaction, so that the self-healing reaction can continue. After the cracks appear, this continuous self-healing reaction can continuously fill and repair the cracks, thereby improving the crack healing rate and permeability recovery rate.

[0051] Comparing Example 3 with Comparative Example 1, it can be seen that when polyethylene terephthalate is prepared directly from polyethylene terephthalate without using modified polyethylene terephthalate-based polymer, the crack healing rate and permeability recovery rate of the cement slurry self-healing agent are significantly reduced.

[0052] Taking Example 3 as the optimal example and combining it with Comparative Example 2, it can be seen that in the preparation method of the modified polyethylene terephthalate-based polymer, when the tetraethyl orthosilicate is removed, the crack healing rate and permeability recovery rate of the cement slurry self-healing agent are significantly reduced; Ethyl orthosilicate is an important silicon source. It generates silica and other silicides through hydrolysis and polycondensation. These silicides can react with calcium, aluminum and other components in cement paste to generate calcium silicate, calcium aluminate and other minerals with gelling properties, thereby improving the crack healing rate and permeability recovery rate. When ethyl orthosilicate is removed, the lack of silicon source leads to a decrease in the generated gelling minerals, which in turn affects the filling and healing effects of cracks, resulting in a significant decrease in the crack healing rate and permeability recovery rate. During the reaction, ethyl orthosilicate forms a three-dimensional network structure, which can enhance the mechanical properties and stability of the modified polyethylene terephthalate-based polymer. At the same time, it can also interweave with the hydration products in the cement paste to form a more compact structure, thereby improving the impermeability and crack healing ability of the cement paste. However, when ethyl orthosilicate is removed, the formation of the three-dimensional network structure is hindered, the performance of the modified polyethylene terephthalate-based polymer decreases, and the reinforcing effect on the cement paste is weakened, resulting in a decrease in the crack healing rate and permeability recovery rate.

[0053] Example 3 is the best example, and combined with Comparative Example 3, it can be seen that in the preparation method of the modified polyethylene terephthalate-based polymer, when the titanate is removed, the crack healing rate and permeability recovery rate of the cementing slurry self-healing agent are significantly reduced; Titanates can significantly promote polymerization reactions, increase the growth rate and cross-linking degree of molecular chains, and thus give polymers better structures and properties; however, when titanates are removed, the polymerization reaction rate decreases significantly, causing the molecular weight distribution of the polymer to become uneven and the degree of cross-linking of the molecular chains to decrease, thereby weakening the mechanical properties and self-healing ability of the polymer, ultimately affecting the crack healing rate and permeability recovery rate; at the same time, titanates can also improve the interfacial bonding between modified polyethylene terephthalate-based polymers and cement stone, and it enhances the bonding tightness between the two by forming a transition layer between the two; however, when titanates are removed, the interfacial bonding weakens, resulting in easy debonding between the self-healing agent and the cement stone, thereby reducing the filling and repairing effect of the self-healing agent on cracks, and further reducing the crack healing rate and permeability recovery rate.

[0054] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A self-healing agent for cementing slurry, characterized in that: The invention comprises the following components: 30-50 parts by weight of a modified polyethylene terephthalate-based polymer, 2-10 parts by weight of a metal oxide, 5-15 parts by weight of a lithium silicate, 0.5-2 parts by weight of a persulfate, 0.1-1 parts by weight of Bacillus subtilis and 1-5 parts by weight of calcium lactate; The modified polyethylene terephthalate-based polymer is prepared by alcoholysis reaction of isosorbide and polyethylene terephthalate, and then mixing with tetraethyl orthosilicate and titanate.

2. The self-healing agent for cementing slurry according to claim 1, characterized in that: The preparation method of the modified polyethylene terephthalate-based polymer is as follows: S1.1, respectively weigh the following components in parts by weight: 50-80 parts by weight of polyethylene terephthalate, 10-30 parts by weight of isosorbide, 1-3 parts by weight of sodium hydroxide, 10-20 parts by weight of tetraethyl orthosilicate, 20-40 parts by weight of toluene, 5-15 parts by weight of titanate, and 0.1-0.5 parts by weight of acetic acid; S1.2, under nitrogen protection, polyethylene terephthalate and isosorbide are mixed, sodium hydroxide with a concentration of 1-3% is added, the temperature is slowly raised to 180-250°C, and agitated at a speed of 300-600 r / min for 3-8 hours to obtain modified polyethylene terephthalate; S1.3, dissolving tetraethyl orthosilicate in toluene to obtain a tetraethyl orthosilicate solution; adding modified polyethylene terephthalate to the tetraethyl orthosilicate solution, lowering the temperature to 80-120° C., and stirring at a speed of 400-800 r / min for 30-60 min to obtain a mixture; S1.4, add titanate to the mixture, add 98% acetic acid after the addition, and continue stirring at 400-800r / min for 10-15min; after mixing evenly, raise the temperature to 120-150℃ and react for 1-3h; S1.

5. After the reaction is completed, the reaction system is subjected to rotary evaporation at 50-80°C and a vacuum degree of 0.08-0.1 MPa to obtain a modified polyethylene terephthalate-based polymer.

3. The self-healing agent for cementing slurry according to claim 2, characterized in that: In the above S1.2, the relative molecular mass of polyethylene terephthalate is 15000-30000.

4. The self-healing agent for cementing slurry according to claim 2, characterized in that: In the step S1.2, the temperature is slowly increased at a rate of 20-30°C / h.

5. The self-healing agent for cementing slurry according to claim 2, characterized in that: In S1.3, the concentration of the ethyl orthosilicate solution is 30-70%.

6. The self-healing agent for cementing slurry according to claim 2, characterized in that: In the above S1.4, the titanate is any one of tetrabutoxy titanate or tetraisopropoxy titanate.

7. The self-healing agent for cementing slurry according to claim 2, characterized in that: In the step S1.4, the time for adding titanate dropwise is 20-40 min.

8. A method for preparing a cementing slurry self-healing agent, used for preparing the cementing slurry self-healing agent as claimed in any one of claims 1 to 7, characterized in that: The preparation method of the cementing slurry self-healing agent is as follows: S2.

1. Weigh the following components in parts by weight respectively: 30-50 parts by weight of modified polyethylene terephthalate-based polymer, 2-10 parts by weight of metal oxide, 5-15 parts by weight of lithium silicate, 0.5-2 parts by weight of persulfate, 0.1-1 parts by weight of Bacillus subtilis and 1-5 parts by weight of calcium lactate; S2.2, uniformly mixing the modified polyethylene terephthalate-based polymer, the metal oxide, the lithium silicate and the persulfate, stirring with a stirrer at a speed of 100-200 rpm for 20-30 min to obtain a dry blend; S2.3, slowly drop the activated Bacillus subtilis suspension into the dry mix, and stir at a speed of 200-300 rpm for 5-10 min; add calcium lactate, and continue stirring at a speed of 200-300 rpm for 10-20 min to obtain a mixture; S2.

4. Place the mixture in an oven and dry it at 40-60°C for 1-2 days to obtain a cementing slurry self-healing agent.

9. The method for preparing the self-healing agent for cementing slurry according to claim 8, characterized in that: In the above-mentioned S2.2, the metal oxide is zinc oxide or magnesium oxide.

10. The method for preparing the self-healing agent for cementing slurry according to claim 8, characterized in that: In S2.3, the activated Bacillus subtilis suspension is slowly added to the dry mix at a rate of 1-5 mL / min.

Citation Information

Patent Citations

  • Preparation method of high-solid-content aqueous polyurethane for leather

    CN102206410A

  • Self-healing cement-based material containing bacterial spores and preparation method thereof

    CN103880370A

  • Preparation method of cement-based material having deep self-repairing function

    CN104261736A

  • Method for preparing self-repairing mortar by using active cement particle microcapsules

    CN118290093A

  • Microbial concrete composition and method of preparation thereof

    IN201811037175A

Cited By

  • Well cementation self-healing cement paste and preparation method thereof

    CN119930216A

  • A self-healing cement slurry for well cementing and its preparation method

    CN119930216B